Beyond a 1000 flowers: The institutionalisation of gender in research programs - Danielsen, K. (International Livestock Research Institute, 2016)
Katrine Danielsen was part of the original team that designed the coaching trajectory. She thinks the approach was successful because it was bottom-up. Individuals who were eager to integrate gender in their technical work were identified and supported through the coaching. The team also also looked beyond projects to institutionalize gender integration and knowledge in the CGIAR research programs. Interview with Katrine Danielsen (Royal Tropical Institute) for the book "A different kettle of fish? Gender integration in livestock and fish research": http://hdl.handle.net/10568/76684